2020
DOI: 10.1016/j.earlhumdev.2020.105138
|View full text |Cite
|
Sign up to set email alerts
|

Second-to-fourth digit ratio and facial shape in Buryats of Southern Siberia

Abstract: Background The 2nd-to-4th digit ratio (2D:4D) is a putative predictor of a prenatal exposure to sex hormones. 2D:4D is sexually dimorphic (males < females). Studies, linking digit ratio and full facial shapes among Europeans, show that a low 2D:4D is associated with a set of male-specific facial features. Buryats – Mongolian people from Southern Siberia – demonstrate a different pattern of facial sexual dimorphism than Europeans (narrower and more vertically elongated faces in men as opposed to wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 62 publications
1
6
1
Order By: Relevance
“…In this study, it was demonstrated that sexual facial dimorphism in Maasai is rather low, compared to Europeans and Asians [ 38 , 124 ], and sex explains 1.8% of the total variance of facial shape in the whole sample (for instance, in Buryats, a Mongolian population of Southern Siberia, sex explains 20% of the total facial shape variance, which was demonstrated using the same configuration of facial landmarks as in the present study [ 124 ]). When the three age cohorts of Maasai were tested separately, it was found that sex differences in facial morphology were minimal (2%) in the youngest age cohort, and increase with age, gaining up to 4% in in elder-adults age cohort.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In this study, it was demonstrated that sexual facial dimorphism in Maasai is rather low, compared to Europeans and Asians [ 38 , 124 ], and sex explains 1.8% of the total variance of facial shape in the whole sample (for instance, in Buryats, a Mongolian population of Southern Siberia, sex explains 20% of the total facial shape variance, which was demonstrated using the same configuration of facial landmarks as in the present study [ 124 ]). When the three age cohorts of Maasai were tested separately, it was found that sex differences in facial morphology were minimal (2%) in the youngest age cohort, and increase with age, gaining up to 4% in in elder-adults age cohort.…”
Section: Discussionsupporting
confidence: 74%
“…Seventy-one facial landmarks and semi-landmarks were manually placed on each photograph using tpsDig2 2.17 [ 123 ]. Landmarks’ positions were set based on the configuration developed by Windhager et al [ 45 ], which has been already used in our earlier studies [ 37 , 121 , 124 ]. This configuration included 37 landmarks, which are known to be classical anthropometrical approximations to cranio-facial and soft-tissue facial shape determinants [ 33 , 45 , 66 , 125 , 126 ] as well as 34 semilandmarks, used for covering facial outline, eye-brows and lips shapes.…”
Section: Methodsmentioning
confidence: 99%
“…Seventy-one anthropometric facial landmarks and semilandmarks were placed on each of the selected photographs in tpsDig 2. 17 (Rohlf, 2015) following configuration developed by Windhager et al (2011), and used previously in our earlier studies (Butovskaya et al, 2018;Rostovtseva et al, 2020aRostovtseva et al, , 2021aRostovtseva et al, , 2021b. The facial configurations were then standardized for the position, orientation, and scale using Generalized Procrustes superimposition with sliding of the semi-landmarks in tpsRelw 1.67 (Rohlf, 2015).…”
Section: Composite Portraits Of Men With Different Leadership Potenti...mentioning
confidence: 99%
“…Faces perceived as untrustworthy had more V-shaped eyes and brows positions (a frown), were more prolonged in vertical direction, had narrower facial outline, especially in the lower face. Generally, the facial shape pattern along trustworthy–untrustworthy vector almost fully corresponded to the facial femininity-masculinity vector for Buryats (see Rostovtseva et al, 2021b; Rostovtseva, Mezentseva, et al, 2020). Earlier studies conducted among representatives of European populations, also demonstrated that facial shape perceived as more trustworthy is female-like (Kleisner et al, 2013; Rostovtseva et al, 2023; Stirrat & Perrett, 2010).…”
Section: Discussionmentioning
confidence: 82%
“…This caused further exclusion of female photographs from the analysis, and the rest of our study focused only on the male part of the Buryat sample, and only on the male-male facial perception. The lack of association between female facial shape and independent biological or behavioral parameters is a very common situation (Mezentseva et al, 2023; Rostovtseva et al, 2021a; Rostovtseva, Mezentseva, et al, 2020). One of the possible reasons for that may be rooted in less general variability in female facial shape compared with male, due to variability in testosterone-mediated facial traits, which is much higher in men.…”
Section: Discussionmentioning
confidence: 99%